A Review on Endodontic Treatment in the Patients with Bleeding Disorders - Nawras Maher Mostafa; Shady Ahmed Moussa Aly (New Horizons in Medicine and Medical Research Vol. 5, 2022)
Bleeding disorders remain an enigma to the dentist’s world over. The dental treatment of patients with bleeding disorders has been widely discussed in the literature with the aim of developing safe dental procedures. They not only challenge the skills of dental specialists but also raise the question of how these individuals should be managed emotionally as well as psychologically. The high incidence of dental problems is inducing bleeding during treatment which can even be life threatening in certain cases. With proper care, diligence and meticulous treatment planning, there is no dental treatment that cannot be performed in such patients. Mild bleeding disorder patients can be easily managed and can effectively undergo even surgical endodontic, however, severe bleeding disorder condition can pose significant health hazard and needs thorough preparation to meet any exigencies arising during the treatment. The majority of literature recommends how to deal with bleeding disorder patients in different cases during endodontic treatment. Non-surgical endodontic treatment of those patients totally safe and should be preferred over extraction as possible and can be done routinely, but for surgical endodontic treatment the consultation of the patient’s hematologist should be considered.